EFFORTS TO IMPROVE STUDENTS' LEARNING UNDERSTANDING OF GRADE IV SD NEGERI 2 KUTABLANG ON THE HUMAN SKELETAL MATERIAL THROUGH TAI TYPE COOPERATIVE LEARNING (TEAM ASSISTED INDIVIDUALIZATION) - Faizah M.Nur; Puji Astuti (Journal of English Education and Social Science, 2024)
The purpose of this study was to find out: improving students' understanding, teacher and student activities and responding to fourth grade students at SD Negeri 2 Kutablang on the Frame of Human Material with Team Assisted Individualization Learning models. The research approach used is a qualitative approach with a type of classroom action research. Data collection techniques are tests, observation sheets and questionnaires. The results showed that: (1) there was an increase in students' understanding of an increase, in the first cycle the percentage of completeness of 66.67% increased to 85.71% in the second cycle. In addition, it can also increase students' understanding in the first cycle of 67.62%, increasing to 77.38% in cycle II. There is an increase in teaching and learning activities between teachers and students has been going well. This can be seen from the results of the first cycle teacher observation of 77.88% and increased to 92.16% in the second cycle. While the results of student observation cycle I amounted to 71.26% and increased to 90.44%. In addition, after all the learning activities were carried out, the use of the Team Assisted Individualization learning model on the subject of skeletal studies in humans turned out to get a positive response from students.